Theoretical and simulation of central elliptical hole with rectangular plate - M Sivaramakrishnaiah; S.N. Pradeepkumar Reddy; P. Madhu Raghava; B.V. Amaranathareddy (Journal of Emerging Science and Engineering, 2024)
A study on design engineering components with slot, notches is very important, because there is a stress increases/failure region area, where the force/stress is concentrating more and more. The elastic stress concentration mainly depends on the mode of loading, materials, and geometry of the design engineering components. The design engineers, academicians, and researchers concentrated and focused on fail-safe design and safe life design. A Plate is considered with different slots, such as circular and elliptical. The main objective of this study is to find out the stress concentration factor in plates with various cutout shapes. This concept is used in design components/structures, for finding the elastic stress concentration. The methods compared are tabulated with their findings. Singularities of the circular hole and elliptical hole in rectangular plates are considered in the present study. The finite Element Method (FEM) was used for fine mesh and ANSYS WORKBENCH software was used for extracting the results and results were validated by analytical or experimental methods.